2007
DOI: 10.1111/j.1365-2036.2007.03290.x
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index differ between patients with Barrett’s oesophagus and patients with chronic gastro‐oesophageal reflux disease?

Abstract: BackgroundObesity has been demonstrated to be a risk factor for the development of gastro-oesophageal reflux disease (GERD).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 26 publications
1
30
0
Order By: Relevance
“…During the past 2 years, several studies examined the association between obesity and Barrett’s oesophagus and arrived at mixed results from a significant risk increase with high BMI,12 13 significant increase with high BMI only in the presence of GORD symptoms,14 or no association 15. Two large case–control studies in the US reported that abdominal diameter but not BMI was an independent risk factor of Barrett’s oesophagus.…”
Section: Association Between Obesity and Gord-related Disordersmentioning
confidence: 99%
“…During the past 2 years, several studies examined the association between obesity and Barrett’s oesophagus and arrived at mixed results from a significant risk increase with high BMI,12 13 significant increase with high BMI only in the presence of GORD symptoms,14 or no association 15. Two large case–control studies in the US reported that abdominal diameter but not BMI was an independent risk factor of Barrett’s oesophagus.…”
Section: Association Between Obesity and Gord-related Disordersmentioning
confidence: 99%
“…Simple obesity, as measured by the body mass index (BMI), has been reported as one of the strongest risk factors for GERD symptoms, erosive esophagitis and esophageal adenocarcinoma [6,7,8,9,10], while it still remains controversial whether it is also an independent risk factor for BE [11,12,13,14,15]. Several studies have examined the association between simple obesity and BE and inconsistent results have been reported, ranging from a significantly increased risk associated with a high BMI [11,12], to a significantly increased risk associated with a high BMI only in the presence of GERD symptoms [13], to no association at all [14]. Our retrospective cohort study in the Japanese general population showed that simple obesity is not a risk factor for BE; the evaluation of the association between BMI and BE may be limited by the small numbers of obese subjects in the Japanese general population (table 1) [15].…”
Section: Simple Obesity and The Risk Of Bementioning
confidence: 99%
“…The cohort in this study is similar in age at diagnosis to others in the UK [68,[110][111][112], the US [72,[113][114][115][116][117][118][119][120][121], France [122], Sweden [71], Switzerland [123,124], Austria [124], Germany [124], the Netherlands [67], Australia [78] and was slightly lower than a multi-centre cohort from Italy [60]. The male:female ratio is comparable to another large UK study [110] and higher than some European studies [60,112] but lower than others [124] and generally lower than in the US [35, 58,59,66,113,120,125].…”
Section: Discussionmentioning
confidence: 99%